Personal Readings and Public Texts: Book Blogs and Online Writing about Literature - Steiner, Ann (Culture Unbound, 2010)
The blogging culture has become an important and integrated part of the book trade and has influenced the publishing, marketing and distribution of literature in North America and in many European countries. However, it is unclear how this potential agency among bloggers operates, and thus far most research has concerned politics, media systems and larger social structures. The present article is a study of the Swedish book blogs during the autumn of 2009 and an attempt to address a small, but significant, part of the Internet influence. The relationship between books and digital technology is complicated and manifold, but it is clear that the Internet has changed how people access books, how they read and how they communicate with others about their reading. Here, the position of the amateur is one that will be discussed in detail in terms of professionalism, strategies and hierarchies. Another issue that will be addressed is the connections between the book bloggers and the book trade, especially the publishers and their marketing departments. The book bloggers operate in a social realm, despite the fact that their writing is personal, and have to be understood in their social, economic and literary context. The Swedish book blogs will be analysed with the help of readerresponse theory, sociology of literature and a book historical perspective on the dissemination of literature.